Pandangan Orang Tua terhadap Perilaku Anak Bermain Game Online Fifa Ultimate Team - Noerabadi, Naufal Azra (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is motivated by the views of parents seeing their children playing online games, especially FIFA Ultimate Team because there are many online and offline tournaments held in Surabaya. The purpose of this study was to determine the perceptions of Surabaya parents towards the FIFA Ultimate Team online game. The research method uses a qualitative approach with a theoretical model by David Krech and Richard S. Cruthfield which is divided into two factors, namely functional and structural factors. Data collection techniques were carried out by in-depth interviews. The results of this study indicate several perceptions of parents who have different perspectives on the FIFA game. Then an opinion emerged stating that in the game FIFA has a player trading system with the aim of teaching children about economics and financial management. However, there are also parents who think that trading in the FIFA game is feared to interfere with their child's academic achievement.